Ministerial decree no. 114/2011 amending the statute of rules enforcing the provisions of the law on import and export = قرار وزاري رقم 114 لسنة 2011 بتعديل لائحة القواعد المنفذة لأحكام قانون الاستيراد والتصدير - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
Ministry of industry and foreign trade decree no. 114 of the year 2011 – وزارة الصناعة والتجارة الخارجية قرار رقم 114 لسنة 2011